Abundant neutrophil extracellular traps in thrombus of patient with microscopic polyangiitis - Nakazawa, Daigo; Tomaru, Utano; Yamamoto, Chiho; Jodo, Satoshi; Ishizu, Akihiro (Frontiers in Immunology, 2012)
This is a case study of a patient diagnosed with microscopic polyangiitis (MPA) and complicated with deep vein thrombosis (DVT), who died of respiratory failure despite treatment. Autopsy revealed severe crescentic glomerulonephritis and massive alveolar hemorrhage. The thrombus contained abundant neutrophils. Although it is reported that patients with ANCA-associated vasculitis (AAV) have an increased risk of DVT, it remains elusive why they are prone to thrombosis. A recent study has demonstrated the presence of neutrophil extracellular traps (NETs), a newly recognized mode of neutrophil cell-death, in glomerular crescents of MPA patients. Interestingly, NETs were identified in the thrombus as well as in the glomerular crescents in the present case. When compared to other thrombi unrelated to MPA, the amount of NETs was significantly greater in the MPA patient. On the other hand, NETs are critically involved in thrombogenesis because histones within NETs can bind platelets and blood coagulants. Although this is important in regard to containment of microbes within NETs, excessive NETs could cause thrombosis. The collective findings suggest the possibility that thrombosis could be critically associated with MPA via NETs, and that NETs could be a therapeutic target in MPA patients.